Single Nucleotide Polymorphism rs10919543 in FCGR2A/FCGR3A Region Confers Susceptibility to Takayasu Arteritis in Chinese Population - Fang Qin; Hu Wang; Lei Song; Xi-Li Lu; Li-Rui Yang; Er-Peng Liang; Wei Wang; Yu-Bao Zou; Jin Bian; Hai-Ying Wu; Xian-Liang Zhou; Ru-Tai Hui; et al. (Chinese Medical Journal, 2016)
Background: Takayasu arteritis (TA) is a rare inflammatory arteriopathy of unknown etiology. The aim of this study was to investigate the genetic susceptibility to TA in a Chinese population. Methods: Four single nucleotide polymorphisms (SNPs) those locate in the IL12B region (rs56167332), the MLX region (rs665268), the FCGR2A/FCGR3A locus (rs10919543), and the HLA-B/MICA locus (rs12524487), associated with TA in different population, were genotyped in 123 Chinese TA patients and 147 healthy controls from January 2013 to August 2014. A Chi-square test was used to test for genotype/allele frequencies variants. Results: Among the four SNPs, rs10919543 was found to be significantly associated with TA in the studied population. The GG genotype of rs10919543 at the FCGR2A/FCGR3A locus is a high risk factor (odds ratio [OR] = 6.532, 95% confidence interval [CI] = 2.402 − 17.763, P < 0.001) for TA. Among TA patients, the level of eosinophil granulocytes (Eos) in the peripheral blood was observed to be higher in the GG group of rs10919543 (n = 23, Eos = 0.11 [0.08, 0.17] ×109/L) than the GA + AA group (n = 100, Eos = 0.08 [0.05, 0.13] ×109/L, P = 0.028). No correlation between the genotypes of the other three SNPs and TA patients was observed. Conclusions: Our findings revealed unique genetic pattern in Chinese TA patients that may be partly responsible for the higher risk of TA in this population. FCGR2A/FCGR3A-related immune disorder might contribute to the etiology of TA.